Evaluation of antifungal activity of neolamarckia macrophylla leaf extract - Michelle, Ngassy Mering (Universiti Malaysia Sarawak (UNIMAS), 2016)
Neolamarckia macrophylla (Roxb.) Bosser is from genus Neolamarckia of the family Rubiaceae. This plant is known as Red Kelampayan among the locals. It is an important tropical tree chosen for reforestation in Malaysia. The aims of this research were extract the antifungal properties of N. macrophylla leaf suing aqueous and methanol extraction followed by the evaluation of antifungal activity of the leaf extracts against Aspergillus flavus, Aslergillus niger and Fusarium solani. Extracts of dirrdernt concentration (12.5 mg/mL, 25 mg/mL, 50 mg/mL and 100 mg/mL) were spread uniformly on the potato dextrose agar. All of the results showed that there is inhibitory effect on the fungi exhibiting percentage within ranges of 4-80% The most effective extraction method to check antifungal activity of N. macrophylla was the aqueous extraction of which the highest perecntage inhintion obtained was 80%. Further studies are needed so that the inconsistency of the results obtained may be reduced and also to improve on the evaluation of the potential of N. macrophylla as antifungal agents.